Estudio de factibilidad para el establecimiento de una empresa de producción y comercialización de hortalizas orgánicas en la Parroquia Juan Montalvo, Cayambe-Ecuador 2010 - Morocho Chiriboga, Marco Efraín (2012)
The project feasibility study for the establishment of a production and marketing of organic vegetables enterprise in Juan Montalvo - Cayambe - Ecuador 2011, aims to raise awareness of the productive capacity of the area where the geographical location, infrastructure, type of soil and climate are favorable for organic vegetable production, activity of small and medium farmers, who for lack of resources made only small tracts of land as intensive monoculture that exists in every sector of Cayambe is dedicated to floriculture and livestock With this background the project is primarily aimed to make a diagnosis of organic vegetable production in the parish of Juan Montalvo, so we can determine the current state of supply, demand and propose improvements in the production and marketing, ensuring profitability of the project.